The Legal Regulation of Islamic Banking in Algerian Legislation and Comparative law: Morocco and Tunisia - Guenfoud, Ramdane; Seffai, Laid (Journal of Legal Studies and Researches, 2023)
The aim of this study is to clarify the legal regulation of Islamic banking. Algeria has issued two legal texts regarding Islamic banking explicitly following law 90-10, in contrast to Moroccan and Tunisian laws that kept it within the provisions of the finance law, despite the attempt to Islamic banking.